Investigating Features of Multilingualism in Ayoade Okedokun’s Mopelola: The Tale of a Beauty Goddess: A Sociolinguistic Appraisal - KOUTCHADE, INNOCENT SOUROU (My University, 2020)
In most African writings, it is commonly noticed that culture and linguistic background affect the creation of literary idiolects. African writers use the English language in accordance with the situation in which they find themselves; they also make use of multilingual features, thus combining the English language with the linguistic resources they draw from their mother tongue. This paper aims to explore patterns of multilingualism in Mopelola: The Tale of a Beauty Goddess, a play produced by a Nigerian writer, Ayoade Okedokun. The paper mainly focuses on the linguistic and cultural influence of Yoruba that reflect the use of multilingualism features in the play. The analysis shows that there are various instances of borrowing, code-switching and transliteration representing the cultural interferences which are used to accommodate some elements of the writer’s native culture and language into the English language.
Keywords: : Multilingualism; Yoruba; Borrowing; Code-switching; Transliteration; Mopelola